Transparency and open government data: A wide national assessment of data openness in Brazilian local governments. Issue 1 (20th March 2017) - Corrêa, Andreiwid Sh.; Paula, Evandro Couto de; Corrêa, Pedro Luiz Pizzigatti; Silva, Flávio Soares Corrêa da
Abstract : Purpose: This paper aims to identify and to understand how current data portals comply with open government data (OGD) principles in the context of Brazilian local government. Design/methodology/approach: In this paper, we assessed a sample of 561 municipalities from a universe of interest of 3, 052 ones expected to disclose information using the internet. As part of our methodology, the authors analyzed the required items for active disclosure and the technical requirements, all enforced by Brazilian law and close to OGD principles which are the focus of analysis of the authors. Findings: The findings generally show the vast majority of assessed data portals did not comply with the basic requirements stated by national law, consequently not complying with OGD principles, and prevent society from benefiting from government data openness. The authors also found arguments that the national law should explicitly reproduce OGD principles, as they demonstrate clearer understanding about the global context of open data. Originality/value: The contributions of this work can be used to plan public data openness actions over the internet and envision effective accountability and public participation with clearer legislation and with the effective implementation of OGD principles in data portals.